A mitochondria-targeted colorimetric and ratiometric fluorescent probe for biological SO2 derivatives in living cells1. Issue 50 (25th June 2015) - Liu, Yu; Li, Kun; Wu, Ming-Yu; Liu, Yan-Hong; Xie, Yong-Mei; Yu, Xiao-Qi
<x xml:space="preserve">Abstract</x> A novel mitochondria-targeted ratiometric fluorescent probe for SO2 derivatives was presented, which could selectively respond to HSO3− over other thiol compounds in living cells.